(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
Hyperglycemia or increased blood sugar levels are diseases characterized by medical conditions with increased blood sugar above normal. One factor that affects blood glucose levels is drinking coffee. This study aimed to determine the description of random blood glucose levels in coffee drinkers and whether they increase or decrease. The method used in this study is a quantitative approach with a descriptive research type. The sampling technique in this study uses a purposive sampling technique, assuming the number of samples is 30 and using univariate test data techniques. The result of the study shows that in coffee drinkers with a sample size of 30, it was found that 22 (80%) coffee drinkers had normal blood glucose levels, and 8 (20%) coffee drinkers had high blood glucose levels.